Interaction: 'Samhandling' Under Risk A Step Ahead of the Unforeseen - Torgersen , Glenn-Egil (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
The authors of Interaction: 'Samhandling' Under Risk. A Step Ahead of the Unforeseen elucidate new views on emergency-preparedness management and understanding the unforeseen in society and learning processes by introducing the concept of 'samhandling', a Norwegian term that connotes interaction, collaboration and cooperation in one word. What are the basic structures of the concept of 'samhandling' under risk? How can 'samhandling' be created when conditions are unpredictable? These questions served as the springboard for 28 research studies, the results of which are now presented in this anthology, organized in four parts: Educational, Organizational, Operational Samhandling Structures and Theory Construction and The Way Forward. The book conveys new knowledge that forms the basis for a new view on strategic, emergency-preparedness management, and understanding of the unforeseen in society and in learning processes. The approach is interdisciplinary but has a particular focus on disciplines such as pedagogy, psychology, military science, health sciences, and organization and management, applied in various industries and sectors related to practical examples, experiences and challenges. The book's primary target group is the scientific research communities within these disciplines.